(untitled) (Journal of Naval Architecture and Marine Engineering, 2021)
In this study, numerical simulations on the noise of the underwater marine propeller for different pressures, skew angles, and performance conditions are investigated. The study has been carried out for the prediction of cavity and noise cavitation characteristics of the propeller. The blade sheet cavitation created by an underwater propeller is then evaluated using numerical analysis. The cavitation and cavity around marine propellers were predicted using MRF (Multiple Reference Frame) techniques. The simulation uses the Reynolds Averaged Navier-Stokes (RANS) formulation with the turbulence model k-ω Shear Stress Transport and the Fast Fourier Transform. The FW-H equation is used to measure far-field radiation under various operating conditions. The simulation is carried out to present that the pressure and skew propeller angles have an effect on the form and area of the cavity, as well as cavitation noise. The noise characteristics at various positions of hydrophones and speeds of the marine propeller are presented. The 3D model of B-series marine propeller with D=250 mm, Z=4, P/D= 1.0, AE/AO=0.55, skew angles of 16, 35, 53, and 72 degrees at advance coefficient, J=0.221, is used for the simulation